Overcome data gaps to benchmark building stocks against climate targets related to the EU taxonomy and other decarbonisation initiatives. Issue 1 (1st September 2022) - Jakob, Martin; Ostermeyer, York; Nägeli, Claudio; Hofer, Christian
Abstract: National disclosure regulation is more and more flanked by stricter requirements of climate reporting. Industry stakeholders with more than 250 employees will for example be required to report on the share of their CAPEX and OPEX that is in line with the 2050 climate targets of the EU. Financial institutions are required to declare how much of their investment is in 2050 target compatible assets. Investment in buildings is an important part of such reporting and there is need of a robust approach and method to be used. The presented project developed such an approach. With reference to the work of the EU Technical Expert Group on Sustainable Finance and the Climate Bond Initiative (CBI), generally applicable criteria for buildings have been determined and calculated for the example of Switzerland. They are based on a best-in-class approach. While the EU Technical Taxonomy refers to the top 15% of buildings in terms of primary energy demand, CBI uses CO2-emissions as a benchmark. To compare the current state of buildings sector with these criteria, a distributional building stock model is used, which also addresses the fact that the data availability on energy efficiency and climate compatibility of the building stock is unsatisfactory in many European countries including Switzerland. To be easily applicable in practice, the criteria are mainly based on two dimensions: on the one hand, on the requirements of codes (in Switzerland the model regulations of the Cantons, MuKEn) and widely used standards and labels (Minergie, GEAK), and on the other hand, on the energy sources used for the generation of space heat and hot water. The study shows that ecologically sustainable, climate-compatible building financing can always be assumed in Switzerland if one of the following two criteria are met for new buildings: multi-family, office or other non-residential buildings according to Minergie from 1998 on, MuKEn from 2000 on or GEAK B that use heat-pumps, wood, pellets or solar energy. Or, any building with Minergie from 2009 on label, MuKEn 2014 or GEAK A that use heat pumps, wood, pellets, solar energy or district heating based on non-fossil energy. In the context of increased pressure on resources, it is important to acknowledge the climate-compatibility of older buildings as well (and to not only consider newly which would generate a bias towards resource intensive building of new houses).